Benchmarking peer-to-peer systems : understanding quality of service in large-scale distributed systems - Steinmetz, Ralf; Strufe, Thorsten; Effelsberg, Wolfgang (Lecture Notes in Computer Science, 2013)
Peer-to-peer systems are now widely used and have become the focus of attention for many researchers over the past decade. A number of algorithms for decentralized search, content distribution, and media streaming have been developed. This book provides fundamental concepts for the benchmarking of those algorithms in peer-to-peer systems. It also contains a collection of characteristic benchmarking results. The chapters of the book have been organized in three topical sections on: Fundamentals of Benchmarking in P2P Systems; Synthetic Benchmarks for Peer-to-Peer Systems; and Application Benchmarks for Peer-to-Peer Systems. They are preceded by a detailed introduction to the subject.